Zooplankton communities of Umiam reservoir, Meghalaya (NE India): composition, abundaqce and ecology - SHARMA, B K; LYNGDH, R M (The Indian Journal of Animal Sciences, 2014)
Zooplankton communities of Umiam reservoir, Meghalaya studied (during November, 1996- October, 1998) at 4sampling stations (I-IV) indicated 16-35 species, wider community similarity (0-86.5%) and comprised 29.2-41.7% ofnet plankton abundance. Rotifera depicted qualitative and quantitative dominance, Cladocera and Copepoda are subdominant groups while Rhizopoda, Ostracoda and Nematoda showed poor densities. ANOYA registered significant variations in zooplankton abundance between months and sampling stations; Rotifera and Cladocera showed significant density differences between months. Zooplankton indicated moderate species diversity, high evenness and low dominance; diversity and dominance recorded significant variations between stations. Multiple regression exhibited higher cumulative influence of 16 abiotic factors (84.0-87.0%) on temporal variations of zooplankton. Q B/T quotient affirmed "mesotrophic" nature of Umiam reservoir.